Toward a Harmonized Approach for Monitoring of Riverine Floating Macro Litter Inputs to the Marine Environment - González-Fernández, Daniel; Hanke, Georg (Frontiers in Marine Science, 2017)
A high percentage of the litter entering the marine environment is assumed to come from land-based sources, but freshwater litter inputs have not been quantified. The lack of data and knowledge on fluxes of riverine litter to the sea, i.e. quantities and sources, hinders implementation of appropriate environmental regulations and mitigation measures. Estimations of riverine litter inputs require a consistent and harmonized approach to gather comparable data. The visual observation of floating litter on rivers has been selected as a simple and robust methodology for litter monitoring. A collaborative network of 32 institutions has been set-up for large spatial coverage. Currently 54 rivers are being observed regularly. A tablet computer application has been developed for the monitoring of floating macro litter (> 2.5 cm) to harmonize the visual observations. The application allows recording of the observed items, their size and geo-position data during monitoring sessions. A common agreed list of litter items and size ranges is used, providing a common harmonized approach for data collection and reporting.